2007
DOI: 10.1002/elan.200603778
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanotubes Paste Electrodes. A New Alternative for the Development of Electrochemical Sensors

Abstract: In this work we summarize the recent activities of our group regarding the analytical performance of a new composite material, the so-called carbon nanotubes paste electrode (CNTPE) obtained by dispersion of multiwall carbon nanotubes in mineral oil. The electrocatalytic properties towards different redox systems, especially those involved in important enzymatic reactions are discussed. Significant shifting in the overpotentials for the oxidation and/or reduction of hydrogen peroxide, NADH, phenol, catechol, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(60 citation statements)
references
References 40 publications
0
55
0
1
Order By: Relevance
“…A variety of carbon-based materials have been introduced recently. These include glassy carbon powder [108], acetylene black [109], template carbon or porous carbon foam [110], doped diamond [111], fullerenes [112], carbon nanofibres [113], and nanotubes [114]. The scope of CPEs has been significantly expanded by the use of ionic liquids [115] or binding agents, like phenantrene, undergoing solidification during carbon paste preparation [116].…”
Section: Notementioning
confidence: 99%
“…A variety of carbon-based materials have been introduced recently. These include glassy carbon powder [108], acetylene black [109], template carbon or porous carbon foam [110], doped diamond [111], fullerenes [112], carbon nanofibres [113], and nanotubes [114]. The scope of CPEs has been significantly expanded by the use of ionic liquids [115] or binding agents, like phenantrene, undergoing solidification during carbon paste preparation [116].…”
Section: Notementioning
confidence: 99%
“…In addition, special attention has been paid to the possibilities of carbon nanotube paste (CNTP)-based electrodes in electrochemical investigations and in modern electroanalysis. Rivas group [16][17][18][19][20][21] has reported on the advantages of CNTP electrode on the electrochemical behavior of different redox systems based on the use of CNTs dispersed in a mineral oil: dopamine, ascorbic acid, dopac and uric acid as well as hydrogen peroxide; 16 guanine, adenine and nucleic acids; 17 phenol, catechol, NADH and hydroquinone; 18 epinephrine and norepinephrine; 19 and glucose. 20 Wang et al reported the use of CNTP electrode for the oxidation of hemocysteine.…”
Section: Introductionmentioning
confidence: 99%
“…However, because both diamond and the binder in such pastes are electric insulators, the functioning of these electrodes remains rather mysterious. In last years, intensively popularized (vi) new forms of carbon complete the list with other pastes made of fullerenes ("C-60" [62,63]), carbon nanoparticles [64], or pastelike mixtures with carbon nanofibers [65], and various types of carbon nanotubes [66]; the latter representing a new phenomenon also within the electrochemistry with carbon pastes, deserving a special attention [2].…”
Section: Carbon Pastes Made Of Alternate Carbonaceous Materialsmentioning
confidence: 99%